IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS LAGU “RUKUN SAMA TEMAN” TERHADAP PERILAKU INTERAKSI SOSIAL MURID KELAS 2B SEKOLAH DASAR - Rachmania Diandini; Reffinka Meisya Iftianingrum; Arfilia Wijayanti; Estiyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the implementation of character education through the song "Rukun Sama Teman" and its impact on the social interaction behavior of grade 2B students in elementary schools. This study uses a qualitative descriptive method with students as research subjects. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the song "Rukun Sama Teman" was implemented consistently in morning habituation activities as well as at the beginning and end of learning. Before the implementation of the song, the percentage of students' social interaction behavior achievement was relatively low, indicated by the components of respecting friends at 54%, cooperation 54%, avoiding conflict 54%, and empathy and caring 57%. After routine habituation, the increase in students' social interaction behavior reached 82% in the components of respecting friends, cooperation 85%, avoiding conflict 83%, and empathy and caring 86%. These results indicate that songs can be an effective medium in character education in